2021
DOI: 10.1136/jim-2021-001854
|View full text |Cite
|
Sign up to set email alerts
|

Nephrosclerosis impacts time trajectory of renal function and outcomes in elderly individuals with chronic kidney disease

Abstract: Despite hypertension ranks among the leading causes of chronic kidney disease (CKD), the impact of chronic hypertensive nephropathy, the so-called ‘nephrosclerosis’ (NS), on CKD progression is often unpredictable, particularly in elderly population. We have conducted a prospective, observational study to define renal function patterns and outcomes in elderly CKD individuals with or without NS. Three hundred four individuals with an already established CKD were categorized according to the etiology of CKD. NS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…The increase in carotid intima-media thickness (IMT) is a good indicator of incipient atherosclerosis. In this setting, another possible early predictor was examined in a population of Ktx recipients [ 13 ]: Cathepsin-K (CatK), a cysteine protease with elastase and collagenase activities involved in vascular remodelling, as well as in the pathogenesis of progressive atherosclerosis [ 14 , 15 ]. This study found that CatK levels in Ktx recipients were lower compared with those in patients on chronic haemodialysis (HD) and comparable to those measured in healthy controls.…”
mentioning
confidence: 99%
“…The increase in carotid intima-media thickness (IMT) is a good indicator of incipient atherosclerosis. In this setting, another possible early predictor was examined in a population of Ktx recipients [ 13 ]: Cathepsin-K (CatK), a cysteine protease with elastase and collagenase activities involved in vascular remodelling, as well as in the pathogenesis of progressive atherosclerosis [ 14 , 15 ]. This study found that CatK levels in Ktx recipients were lower compared with those in patients on chronic haemodialysis (HD) and comparable to those measured in healthy controls.…”
mentioning
confidence: 99%
“…Foi observada perda de função renal por ano menor do que o habitual do serviço, o que justificaria não termos encontrado correlação entre oxalúria e perda de função, visto que em 24 pacientes, quase metade da amostra, sequer houve diminuição da filtração glomerular para comparação. Ao observarmos a literatura, a média de perda de função de 1,2 ml/min/1,73m² foi similar ao encontrado em alguns trabalhos 78,79,80 e inferior à maioria dos artigos encontrados nos últimos anos 81,82,83,84,85,86,87 .…”
Section: Discussionunclassified